Biomechanical sensing of in vivo magnetic nanoparticle hyperthermia-treated melanoma using magnetomotive optical coherence elastography - Huang, Pin-Chieh (Theranostics, 2021)
Rationale: Magnetic nanoparticle hyperthermia (MH) therapy is capable of thermally damaging tumor cells, yet a biomechanically-sensitive monitoring method for the applied thermal dosage has not been established. Biomechanical changes to tissue are known indicators for tumor diagnosis due to its association with the structural organization and composition of tissues at the cellular and molecular level. Here, by exploiting the theranostic functionality of magnetic nanoparticles (MNPs), we aim to explore the potential of using stiffness-based metrics that reveal the intrinsic biophysical changes of in vivo melanoma tumors after MH therapy. Methods: A total of 14 melanoma-bearing mice were intratumorally injected with dextran-coated MNPs, enabling MH treatment upon the application of an alternating magnetic field (AMF) at 64.7 kHz. The presence of the MNP heating sources was detected by magnetomotive optical coherence tomography (MM-OCT). For the first time, the elasticity alterations of the hyperthermia-treated, MNP-laden, in vivo tumors were also measured with magnetomotive optical coherence elastography (MM-OCE), based on the mechanical resonant frequency detected. To investigate the correlation between stiffness changes and the intrinsic biological changes, histopathology was performed on the excised tumor after the in vivo measurements. Results: Distinct shifts in mechanical resonant frequency were observed only in the MH-treated group, suggesting a heat-induced stiffness change in the melanoma tumor. Moreover, tumor cellularity, protein conformation, and temperature rise all play a role in tumor stiffness changes after MH treatment. With low cellularity, tumor softens after MH even with low temperature elevation. In contrast, with high cellularity, tumor softening occurs only with a low temperature rise, which is potentially due to protein unfolding, whereas tumor stiffening was seen with a higher temperature rise, likely due to protein denaturation. Conclusions: This study exploits the theranostic functionality of MNPs and investigates the MH-induced stiffness change on in vivo melanoma-bearing mice with MM-OCT and MM-OCE for the first time. It was discovered that the elasticity alteration of the melanoma tumor after MH treatment depends on both thermal dosage and the morphological features of the tumor. In summary, changes in tissue-level elasticity can potentially be a physically and physiologically meaningful metric and integrative therapeutic marker for MH treatment, while MM-OCE can be a suitable dosimetry technique.